5m-1=-1m+6

Simple and best practice solution for 5m-1=-1m+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m-1=-1m+6 equation:



5m-1=-1m+6
We move all terms to the left:
5m-1-(-1m+6)=0
We get rid of parentheses
5m+1m-6-1=0
We add all the numbers together, and all the variables
6m-7=0
We move all terms containing m to the left, all other terms to the right
6m=7
m=7/6
m=1+1/6

See similar equations:

| 4-2(6)=x | | X+31=4x+14 | | 5m-1=-2+6 | | 17u=32+9u | | w/4-2=15 | | 8x+2(3x-2)=10 | | 5+6x=16x-15 | | -2x-1=-9-1 | | 17=3x+3x-1 | | 7-9m=43 | | 48=6x+7x+9 | | -2x+x=3x-10+x | | 2b=2b-56 | | x-5+6x=72 | | 59=3y÷3 | | 4 | | a/10=7 | | Y+45=3y | | 4x-7+2x-23=180 | | 3c^2+12c+8=0 | | w+73=3w-57 | | 9=r=17 | | 9x-x=3x-54-x | | 0.5(4x+8)=24 | | 2x-85=239 | | x+x+x+x+10=25+x | | (4)x=320 | | 1+3+-5x=44+5x | | 7(3+24n)=21 | | 5z-1=3z+27 | | -69(8x-3)=114 | | 2+(2x5)=14 |

Equations solver categories